Enhancing Intercultural Literacy Among English Language Education Students: A Comprehensive Study at University of Singaperbangsa Karawang - Srisudarso, Mansyur; Miftakh, Fauzi; Dewi, Indah Purnama (Journal of English Language and Education, 2025)
This article examines the development of intercultural literacy among students in the English Language Education Program at the Faculty of Teacher Training and Education of Universitas Singaperbangsa Karawang. Using a mixed-method approach, this research explores students' awareness, understanding, and application of intercultural competence in both local and global contexts. The findings reveal that while most students recognize the importance of intercultural literacy, significant gaps remain in its practical implementation. The study offers strategies for enhancing intercultural communication skills through international exchange programs and experiential learning activities. It recommends strengthening the intercultural components of the curriculum to better equip students to become culturally competent educators in multicultural environments.